Climatic controls on Later Stone Age human adaptation in Africa's southern Cape. Issue 114 (January 2018) - Chase, Brian M.; Faith, J. Tyler; Mackay, Alex; Chevalier, Manuel; Carr, Andrew S.; Boom, Arnoud; Lim, Sophak; Reimer, Paula J.
Abstract: Africa's southern Cape is a key region for the evolution of our species, with early symbolic systems, marine faunal exploitation, and episodic production of microlithic stone tools taken as evidence for the appearance of distinctively complex human behavior. However, the temporally discontinuous nature of this evidence precludes ready assumptions of intrinsic adaptive benefit, and has encouraged diverse explanations for the occurrence of these behaviors, in terms of regional demographic, social and ecological conditions. Here, we present a new high-resolution multi-proxy record of environmental change that indicates that faunal exploitation patterns and lithic technologies track climatic variation across the last 22, 300 years in the southern Cape. Conditions during the Last Glacial Maximum and deglaciation were humid, and zooarchaeological data indicate high foraging returns. By contrast, the Holocene is characterized by much drier conditions and a degraded resource base. Critically, we demonstrate that systems for technological delivery – or provisioning – were responsive to changing humidity and environmental productivity. However, in contrast to prevailing models, bladelet-rich microlithic technologies were deployed under conditions of high foraging returns and abandoned in response to increased aridity and less productive subsistence environments. This suggests that posited links between microlithic technologies and subsistence risk are not universal, and the behavioral sophistication of human populations is reflected in their adaptive flexibility rather than in the use of specific technological systems.